2007
DOI: 10.1080/09540120600677987
|View full text |Cite
|
Sign up to set email alerts
|

Constraints to educational opportunities of orphans: a community-based study from northern Uganda

Abstract: The objective of this article is to assess constraints on educational opportunities of orphans cared for within the extended family system in Lira district, northern Uganda. The data were collected through: review of school census records; ethnographic fieldwork; in-depth interviews with 21 community leaders, 45 heads of households caring for orphans and 35 orphans. Focus group discussions were held with men and women caring for orphans, community leaders and orphans. A household survey was conducted in 402 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 15 publications
(13 reference statements)
1
37
0
Order By: Relevance
“…Qualitative evidence suggests that poor children or orphaned children may engage in a relationship with an older partner (often called a 'sugar daddy' or 'sugar mummy') to fund school or other expenses (Muula et al 2003;Oleke et al 2007). Such a pattern of gift-giving and financial support can encourage lower condom use (Jewkes et al 2001).…”
Section: Older Sexual Partners Sugar Daddies and Sugar Mummiesmentioning
confidence: 99%
“…Qualitative evidence suggests that poor children or orphaned children may engage in a relationship with an older partner (often called a 'sugar daddy' or 'sugar mummy') to fund school or other expenses (Muula et al 2003;Oleke et al 2007). Such a pattern of gift-giving and financial support can encourage lower condom use (Jewkes et al 2001).…”
Section: Older Sexual Partners Sugar Daddies and Sugar Mummiesmentioning
confidence: 99%
“…Abject poverty creates a new lifestyle of hardships to which many of the children may not have been exposed hitherto. The poverty and apathy are exacerbated by subsequent loss of property left behind by their parents because most relatives and caregivers divide it among themselves exploiting the children because of their ignorance, and vulnerability which compounds their misery (WHO 2002, Zimmer and Dayton 2005, Wiegers et al 2006, Landry et al 2007, Oleke et al 2007, Oduaran 2008. Some of the property is sold in an effort to raise some income for the household needs including caring for the sick family members.…”
Section: Challenges Of Aids Orphans and Caregivingmentioning
confidence: 97%
“…Hardships faced by the orphans in most SSA countries are numerous and in magnitudes never imagined a few decades ago (WHO 2002, Nyambedha et al 2003, Zimmer and Dayton 2005, Wiegers et al 2006, Landry et al 2007, Oleke et al 2007, Clacherty 2008. Broadly, they are categorized as psychosocial, socioeconomic, and emotional.…”
Section: Challenges Of Aids Orphans and Caregivingmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite community efforts to respond to the needs of orphans and other vulnerable children, support structures are overburdened with the rapidly growing number of orphans and diminishing resources as a result of the effects of HIV/ AIDS (UNICEF 2015). In earlier studies, Oleke et al (2007) and Thurman et al (2008) found that as a result of poverty many caregivers were unable to provide the orphans in their care with food, medical care, clothing and education, which were needed. Some caregivers were unable to provide for their own children and that had a negative impact on their support of orphans in the community (Thurman et al 2008).…”
Section: Introductionmentioning
confidence: 99%